1991
DOI: 10.1177/0148558x9100600109
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Confirmation Response Rates: Prenotifications, Monetary Incentives and Addressee Differences

Abstract: This article reports the results of a research effort that measured the response enhancing effectiveness of two sizes of small monetary incentives and prenotification letters. The measurements were obtained during the audit of the installment and commercial loan balances of a medium-sized bank located in Central Florida. The data were analyzed with logistic regression. The analyses revealed that prenotification letters tended to encourage timely responses but they did not increase overall response levels. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The results support prior accounting research (e.g., Engle 1991) in finding that the use of small monetary incentives significantly increased confirmation response rates, and that the use of a quarter was as equally effective as a dollar. Additionally, this investigation demonstrated that small monetary incentives could effectively improve response rates with a recipient population consisting of a cross-section of commercial businesses, governmental organizations, and not-for-profit entities.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The results support prior accounting research (e.g., Engle 1991) in finding that the use of small monetary incentives significantly increased confirmation response rates, and that the use of a quarter was as equally effective as a dollar. Additionally, this investigation demonstrated that small monetary incentives could effectively improve response rates with a recipient population consisting of a cross-section of commercial businesses, governmental organizations, and not-for-profit entities.…”
Section: Discussionsupporting
confidence: 85%
“…The lack of a sizable number of negative comments is consistent with Engle (1991) and argues against any beliefs that auditors should not use incentives because they will insult the confirmation recipients and be viewed as unprofessional.…”
Section: Testing For Response Ratesmentioning
confidence: 67%
See 2 more Smart Citations